Diasporic Relationships and Processes: South Asian young adults in Denmark - Singla, Rashmi (Kvinder, Køn & Forskning, 2010)
Diasporic Relationships and Processes: South Asian young adults in Denmark. The article explores social psychological aspects concerned with diasporic relationships among the South Asian diaspora in Denmark and is a follow up of a study conducted in the midnineties. The first wave focussed on the intergenerational relations within the double challenge perspective dealing with age transition and ethnic belonging while the second wave focuses at the relationships across the borders within a theoretical framework of life course perspectives combined with diaspora conceptualisations. In-depth interviews were conducted and analysed through meaning condensation. The gendered experiences of the young adults perceived as active actors indicate reinterpretation of the self, others and home. The results depict that the young adults’ relationships involve both the country of origin and the Danish welfare society, though refutes the myth of return, in spite of Denmark turning increasingly restrictive in migration policies in the past years.